Evaluation of Water Quality in a Highly Impacted Urban Stream Using Water Quality Index (Ankara Stream, Türkiye) - Hazal Aydogdu Kayadelen; Nilsun Demir (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2024)
Population growth along with other factors such as industrial, agricultural, and urban development, threaten freshwater resources in urban areas. Protecting urban water quality for ecological balance, water security, and energy production is crucial. The water quality index (WQI) provides an effective tool for assessing and managing water quality, and the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) is one of the extensively used method. In this study, the pollution status of the Ankara Stream which flows through the densely populated Ankara was examined using physico-chemical parameters collected from five stations (S1-S5), and the water quality status was estimated via CCME-WQI. The results revealed varying water quality across different points on the stream. S2, located in a protected area, exhibited the best quality; in contrast, S4 and S5, located downstream of a wastewater treatment plant, exhibited the poorest quality. The consistency of these findings with the literature and the historical records of Ankara Stream emphasize that the CCME-WQI can be used for the management of water resources with high levels of pollution. This study contributes to sustainable water management practices and highlights the need for advanced treatment techniques to control pollution in urban freshwater resources.